Curcumin attenuates memory deficits and the impairment of cholinergic and purinergic signaling in rats chronically exposed to cadmium. Issue 1 (23rd November 2015) - da Costa, Pauline; Gonçalves, Jamile F.; Baldissarelli, Jucimara; Mann, Thaís R.; Abdalla, Fátima H.; Fiorenza, Amanda M.; da Rosa, Michelle M.; Carvalho, Fabiano B.; Gutierres, Jessié M.; de Andrade, Cinthia M.; Rubin, Maribel A.; Schetinger, Maria Rosa C.; et al.
ABSTRACT: This study investigated the protective effect of curcumin on memory loss and on the alteration of acetylcholinesterase and ectonucleotidases activities in rats exposed chronically to cadmium (Cd). Rats received Cd (1 mg/kg) and curcumin (30, 60, or 90 mg/kg) by oral gavage 5 days a week for 3 months. The animals were divided into eight groups: vehicle (saline/oil), saline/curcumin 30 mg/kg, saline/curcumin 60 mg/kg, saline/curcumin 90 mg/kg, Cd/oil, Cd/curcumin 30 mg/kg, Cd / curcumin 60 mg/kg, and Cd / curcumin 90 mg/kg. Curcumin prevented the decrease in the step‐down latency induced by Cd. In cerebral cortex synaptosomes, Cd‐exposed rats showed an increase in acetylcholinesterase and NTPDase (ATP and ADP as substrates) activities and a decrease in the 5′‐nucleotidase activity. Curcumin was not able to prevent the effect of Cd on acetylcholinesterase activity, but it prevented the effects caused by Cd on NTPDase (ATP and ADP as substrate) and 5′‐nucleotidase activities. Increased acetylcholinesterase activity was observed in different brain structures, whole blood and lymphocytes of the Cd‐treated group. In addition, Cd increased lipid peroxidation in different brain structures. Higher doses of curcumin were more effective in preventing these effects. These findings show that curcumin prevented the Cd‐mediated memory impairment, demonstrating that this compound has a neuroprotective role and is capable of modulating acetylcholinesterase, NTPDase, and 5′‐nucleotidase activities. Finally, it highlights the possibility of using curcumin as an adjuvant against toxicological conditions involving Cd exposure. © 2015 Wiley Periodicals, Inc. Environ Toxicol 32: 70–83, 2017.